Governo eletrônico: estudo sobre os serviços disponíveis no website da secretaria de finanças do município de Belém/PA - PINTO, Adélia de Moraes (Universidade Federal do Piauí, 2022)
This paper is a research about the services available in the website of the Finance Department of Belém/Pará city (Secretaria de Finanças – SEFIN) in the perspective of the Electronic Government platform (e-Gov). This tool has been used by the public anagement in order to provide information and public services to the citizens by using Communication and Information Technologies (TIC), bringing together government and technology. The data collected for this research are a result of observations made in the SEFIN website and from interviews directed to the managers/workers and citizens in order to acknowledge this type of service reality in the city Department. Considering the scenario of the TIC impact in the public management, the main objective of this work is the analysis of the online services availability, particularly in the way they are offered to the citizens by the e-Gov. It is intended to identify which services are provided by the electronic government based on the e-Service (e-A), Ease of Use (FU) and reliability (CO) indicators, as well as describe the SEFIN potential users profile. This department managers perceptions about the users were also evaluated, based on the existing literature about the e-Gov. Methodologically, this research uses the qualitative and quantitative approach on two exploratory steps: website analysis and interviews with the services users and the city department managers/workers. The results show that the city department provides the online services to the citizens, however, despite the managers claims that the communication and information systems of the department work well, for the users, the access to all the provided resources in the website fall short. The highlight is the fact that the SEFIN website shows frequent connection failures, besides the lack of information about the services operation. It is also concluded that regardless the SEFIN efforts and limitations in the services availability to the citizens via internet, even in a rudimentary form, the main concept of the electronic government has been developed in the municipal management. Nevertheless, the managers need to understand that they can use this resource as an efficient tool to remote services provision, on behalf of the public management and the citizens.